ATM-MACHINE (Automatic Tofu Maker Machine) - Agustyan, Adithio (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Automatic Tofu Maker or ATM- Machine (Automatic Tofu Maker â machine) is applied technology to solve problem for traditional tofu factory named Sari Rasa, located in Sindang Sari, Cileunyi, Bandung, West Java. Tofu maker traditionally, producing tofu consist of six steps : milling, boiling, filtering, coagulating, pressing, and colouring. Each step is done separately, by manual operation. With this ATM-Machine, those six steps of producing tofu could be done automatically in a consecutive process. The four process milling, boiling, filtering, and coagulating combine in one process. Compare with traditional one, this ATM-Machine have some advantageous. The production time is shorter, more hygiene, can be operated by one person, and the space used is smaller. Another positive point, traditional boiling systems substituted by used boiler which the fuel needed reduced, and the efficiency of the boiler is between 70% to 90%. Keywords: Automatic Tofu Maker Machine, reducing steps, hygiene, more efficiency